44 Scotland Street [compact disc, unabridged] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- 44 Scotland Street series., 2005)
Welcome to 44 Scotland Street, home to some of Edinburgh's most colorful characters. There's Pat, a twenty-year-old who has recently moved into a flat with Bruce, an athletic young man with a keen awareness of his own appearance. Their neighbor, Domenica, is an eccentric and insightful widow. In the flat below are Irene and her appealing son Bertie, who is the victim of his mother<U+2019>s desire for him to learn the saxophone and italian<U+2013>all at the tender age of five. Love triangles, a lost painting, intriguing new friends, and an encounter with a famous Scottish crime writer are just a few of the ingredients that add to this delightful and witty portrait of Edinburgh society, which was first published as a serial in The Scotsman newspaper.